Зарубіжні теорії менеджменту освітніх інновацій - Листопад, Олена (Studies in Comparative Education, 2013)
Статтю присвячено аналізу сучасних зарубіжних теорій управління інноваційними процесами в освіті; систематизації концепцій, покладених в основу менеджменту освітніх інновацій; екстраполяції підходів зарубіжного менеджменту інновацій на освітню сферу з метою виявлення пріоритетних завдань модернізації сучасного управління освітою. Статья посвячена анализу зарубежных теорій управления инновационными процесами в образовании; систематизации концепцій, положеннях в основу менеджмента инноваций в образовании; экстраполяции подходов зарубежного менеджмента инноваций на сферу образования с целью определения приоритетных задач модернизации современного управления образованием. The paper is dedicated to analysis of foreign educational innovation management; systematization of concepts which lay in the foundation of educational innovation management; extrapolation of the foreign approaches of innovation management on education, aimed at distinguishing the primary tasks of modern education management modernization. The paper illustrates that innovation management in education is substantiated by concepts of innovation management and educational leadership in general lays in modeling of innovation process on macro-, meso-, micro-levels of educational system; organizing and carrying out a system of influences that ensure the realization of innovation idea, its transformation into innovation product which has economic value and provides competitive edge to education. Modern theories of innovation management (institutional, fashion, rational management, management of organizational culture) are discussed in this paper. We attempt to make the case that: the process of innovation management has a cyclic character; consecutive change of stages leads to transformation of theoretical concepts of innovation management into practical actions which, followed by analysis and development, enrich the theoretical plane of innovation process management; ensure the formation new concepts and theories. This paper aims to elaborate a complex of interrelated concepts of innovation management: Customer-based Innovation, Proactive Business Model Innovation, Frugal Innovation, High Speed/Low Risk Innovation, Integrated Innovation. We argue that prognostic analysis of innovation management theory and practice, its key changes and transformations are presented in the theory of innovation development management by a complex of these concepts. This paper presents also that extrapolation of foreign innovation management approaches on the sphere of education allows to consider transition from understanding innovation process as the one to be implicated form outside to viewing it as that capable of self-development, which requires mastering the techniques of innovation process modeling on microlevel (local), substantiated by concepts of innovative leadership theory to be its primary objective.